Analysis of Directives Speech Act Found in Little Women Movie Script - Sanjiwani, Ni Luh Putu Silvia; Ariyaningsih, Ni Nyoman Deni; Utami, Ni Made Verayanti (Institut Pariwisata dan Bisnis Internasional, 2024)
This study concern with analyzed the research entitled An Analysis of Directives Speech Act Found in Little Women Movie Script. This research concerned with identifying the directives speech act used by the characters and how often the types of directives speech act occurred and which types are most frequent appeared in the movie script. This research utilized qualitative method, which is the data were achieved by read the movie script attentively. And also, to present the percentages of result in numerical form, the analysis used quantitative method. Four types of directives speech act were discovered in the utterance of the characters in the Little Women movie script as a result of this analysis. Those are: suggest, order, command, request.